Clinical Application of Immunofluorescence I. Grouping β-Hemolytic Streptococci - Smith, Thomas B. (1965)
Smith, Thomas B. (Armed Forces Institute of Pathology, Washington, D.C.). Clinical application of immunofluorescence. I. Grouping β-hemolytic streptococci. J. Bacteriol. 89:198–204. 1965.—Procedures are described for the production of antistreptococcal serum in rabbits and for the preparation of group-specific conjugates for Lancefield groups A, C, and G. A modification of the conventional technique of absorption and inhibition to prevent cross-reactions with common antigens was used with excellent results. In addition, a promising new approach to eliminating cross-reactions of group A conjugate with antigens of groups C and G by dilution with group A-variant antiserum was tested. A complete method is introduced that enables the clinical laboratory to report whether group A streptococci are present in a given throat culture well within 24 hr after the physician collects the sample.